Kontribusi Fuqaha’ dalam Pengembangan Ekonomi Syariah: Studi Pemikiran Abu Hanifah - Fachrurazi; Ismanto, Kuat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This paper aims to explore the thoughts of Abu Hanifah in the field of Islamic economics and business. This study was carried out within the framework of library research with a qualitative-historical approach. Abu Hanifah’s Book is the main source of data in this study. Secondary data in the form of books, articles, and other documents related to his thoughts, are involved as supporting data. A content analysis strategy is used to discuss the data obtained to draw conclusions. Results of this study indicate that Abu Hanifah is a fiqh expert who contributes to Islamic economic and business thought. Although some authors place him as an early phase of Islamic economics, other facts show that Abu Hanifah's works are mostly in the areas of aqidah and fiqh. The economic problems are only found in the works of his students. The economic thought that he contributed has a normative-ethical fiqh pattern. Nonetheless, its contribution is beneficial to economic development in the past, present, and in the future. This finding implies that the conception developed by classical scholars still finds relevance to be used as a guide in the future development of Islamic economics.